Uji Stabilitas Dan Aktivitas Antioksidan Mikroemulsi Likopen Tomat (Solanum lycopersicum L.): Stability Test and Antioxidant Activity of Tomato Lycopene (Solanum lycopersicum L.) Microemulsion - Evi Sulastri; Mohamad Ikram; Yuliet Yuliet (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2017)
Lycopene is a class of keratonoid that have been proven has antioxidant activity but has limited solubility in water. So as to boost their solubility, in this study conducted in the form of microemulsion formulations. This study aims to get a tomato lycopene extract microemulsion which is stable and has antioxidant effects. The research was initiated to test the antioxidant power of tomato lycopene extract in vitro against DPPH. Tomato lycopene extract microemulsion is formulated based on the optimization of the composition of the base consisting of the VCO as the oil phase, tween 80 as surfactant and glycerin as cosurfactant. Preparations produced were tested for antioxidant activity and their physical and chemical stability testing which include: organoleptic, viscosity, globule size and pH during 28 days of storage. The results showed that tomato lycopene extract formula microemulsion stable composition of tomato lycopene extract 0.3%, VCO 15%, tween 80% and 35% glycerin. The test results obtained physical stability of the microemulsion formula elected tomato lycopene extract has a distinctive scent of aromatic, orange, thick, globule size of <5 μm, viscosity (600, 33 ± 69.29 to 746 cPs ± 8.32), and pH ( 6.27 ± 0.20 to 6.79 ± 0.10). As very strong antioxidant activity with IC50 value of 29.07 ppm.